Intrahospital transport of critically ill patients: A survey of emergency nurses. Issue 5 (10th February 2021) - Hu, Yingli; Shi, Donglei; You, Lili; Li, Wei
Abstract: Background: Despite the frequency of its occurrence, few Chinese studies examined the status of intrahospital transport (IHT) of critically ill emergency room patients. Aims and objectives: To investigate the current status of IHT of critically ill patients and emergency nurses' perception of IHT across China; explore the perceived associations of written protocols with adverse events during IHT; and compare regional differences in IHT of critically ill patients across China. Design: A self‐report questionnaire was conducted among the attendees of a large emergency medicine conference in Beijing in May 2015. Methods: The data, collected through convenience sampling, were analysed using descriptive statistics. Categorical variables were compared using the chi‐squared test. Results: Of the 528 participants from 142 hospitals whose data were analysed, 19.3% considered all nurses competent enough to perform IHT of critically ill patients without special training, and 7.6% even considered nursing students capable of the task. The absence of written transport protocols was perceived to be significantly associated with the occurrence of adverse events such as oxygen supply depletion and incorrect destination. Hospitals in the western region were less likely to have established written IHT protocols and emergency checklists than those in the eastern region. Conclusions: Safe IHT of critically ill patients in the emergency department involves enormous challenges. The results of this survey can facilitate a preliminary understanding of the characteristics and current situation of IHT in emergency settings across China. Relevance to clinical practice: The establishment of standard transport protocols may help reduce the incidence of adverse events.